Treatment of Mycoplasma genitalium. Observations from a Swedish STD clinic. - Carin Anagrius (Public Library of Science (PLoS), 2013)
Objectives To evaluate therapy for Mycoplasma genitalium infection with doxycycline or azithromycin 1 g compared to five days of azithromycin (total dose 1.5 g). Methods A retrospective case study was performed among patients attending the STD-clinic in Falun, Sweden 1998-2005. All patients with a positive PCR test for M. genitalium were routinely offered a test of cure (toc). Response to doxycycline for 9 days, azithromycin 1 g single dose and extended azithromycin (500 mg on day 1 followed by 250 mg o.d. for 4 days) was determined. In patients with treatment failure after azithromycin, macrolide resistance was monitored before and after treatment. Furthermore, the rate of macrolide resistance was monitored for positive specimens available from 2006-2011. Results The eradication rate after doxycycline was 43% (48% for women and 38% for men), for azithromycin 1 g 91% (96% for women and 88% for men) and for extended azithromycin 99% (100% for women and 93% for men). Macrolide resistance developed in 7/7 examined (100%) of those testing positive after azithromycin 1 g, but in none of those treated with extended azithromycin. Macrolide resistance before treatment increased from 0% in 2006 and 2007 to 18% in 2011. Conclusions These findings confirm the results from other studies showing that doxycycline is inefficient in eradicating M. genitalium. Although azithromycin 1 g was not significantly less efficient than extended dosage, it was associated with selection of macrolide resistant M. genitalium strains and should not be used as first line therapy for M. genitalium. Monitoring of M. genitalium macrolide resistance should be encouraged.